Diverse Patterns and Clinical Significance of 11C-Methionine PET in Dysembryoplastic Neuroepithelial Tumors. (30th December 2022) - Kim, Joo Whan; Kang, Yeon-koo; Paeng, Jin Chul; Kim, Seung-Ki; Lim, Byung Chan; Kim, Ki Joong; Phi, Ji Hoon
Abstract : Purpose: Dysembryoplastic neuroepithelial tumors (DNETs) are slow-growing epilepsy-associated tumors. Low or normal 11 C-methionine (MET) PET uptake helps to differentiate DNETs from other low-grade gliomas. However, diverse MET-PET uptake in DNETs has been observed. The aim of this study is to measure the clinical significance and prognostic value of MET-PET in DNET management. Patients and Methods: Retrospective review of 26 DNET patients was done. Clinical characteristics, radiologic findings, and visual and quantitative MET-PET results were analyzed. PET uptake was calculated as the tumor–to–homotopic mirror ratio (TNRm ) and tumor–to–contralateral cortex ratio (TNRc ). The clinical activity of the tumors at the time of PET was classified into active and quiescent groups. The surgical outcome was defined as a composite of 2 different aspects: tumor progression and/or clinical events such as seizure recurrence or tumor bleeding. Results: Twenty-seven MET-PET examinations (20 initial MET-PET and 7 MET-PET during follow-up) were included. Clinically active tumors at the time of PET presented significantly higher values of TNRm and TNRc than quiescent tumors. High MET-PET uptake by visual grading, TNRm ≥ 1.90, and TNRc ≥ 1.85 exhibited poor prognosis for event-free survival. Conclusions: MET-PET uptake correlates well with the clinical behavior of DNETs at the time of PET examination. Moreover, High MET-PET uptake is closely related to seizure recurrence if tumors are not entirely resected. Efforts to achieve gross total resection should be made for DNETs with high MET-PET uptake.